An Aerobic Hybrid Phthalate Degradation Pathway via Phthaloyl-Coenzyme A in Denitrifying Bacteria - Ebenau-Jehle, Christa (Appl Environ Microbiol, 2020)
The degradation of the xenobiotic phthalic acid esters by microorganisms is initiated by the hydrolysis to the respective alcohols and ortho-phthalate (hereafter, phthalate). In aerobic bacteria and fungi, oxygenases are involved in the conversion of phthalate to protocatechuate, the substrate for ring-cleaving dioxygenases. In contrast, anaerobic bacteria activate phthalate to the extremely unstable phthaloyl-coenzyme A (CoA), which is decarboxylated by oxygen-sensitive UbiD-like phthaloyl-CoA decarboxylase (PCD) to the central benzoyl-CoA intermediate. Here, we demonstrate that the facultatively anaerobic, denitrifying Thauera chlorobenzoica 3CB-1 and Aromatoleum evansii KB740 strains use phthalate as a growth substrate under aerobic and denitrifying conditions. In vitro assays with extracts from cells grown aerobically with phthalate demonstrated the succinyl-CoA-dependent activation of phthalate followed by decarboxylation to benzoyl-CoA. In T. chlorobenzoica 3CB-1, we identified PCD as a highly abundant enzyme in both aerobically and anaerobically grown cells, whereas genes for phthalate dioxygenases are missing in the genome. PCD was highly enriched from aerobically grown T. chlorobenzoica cells and was identified as an identical enzyme produced under denitrifying conditions. These results indicate that the initial steps of aerobic phthalate degradation in denitrifying bacteria are accomplished by the anaerobic enzyme inventory, whereas the benzoyl-CoA oxygenase-dependent pathway is used for further conversion to central intermediates. Such a hybrid pathway requires intracellular oxygen homeostasis at concentrations low enough to prevent PCD inactivation but sufficiently high to supply benzoyl-CoA oxygenase with its cosubstrate. IMPORTANCE Phthalic acid esters (PAEs) are industrially produced on a million-ton scale per year and are predominantly used as plasticizers. They are classified as environmentally relevant xenobiotics with a number of adverse health effects, including endocrine-disrupting activity. Biodegradation by microorganisms is considered the most effective process to eliminate PAEs from the environment. It is usually initiated by the hydrolysis of PAEs to alcohols and o-phthalic acid. Degradation of o-phthalic acid fundamentally differs in aerobic and anaerobic microorganisms; aerobic phthalate degradation heavily depends on dioxygenase-dependent reactions, whereas anaerobic degradation employs the oxygen-sensitive key enzyme phthaloyl-CoA decarboxylase. We demonstrate that aerobic phthalate degradation in facultatively anaerobic bacteria proceeds via a previously unknown hybrid degradation pathway involving oxygen-sensitive and oxygen-dependent key enzymes. Such a strategy is essential for facultatively anaerobic bacteria that frequently switch between oxic and anoxic environments.